Challenging intraoperative management of pelvic resection type I,II on 33 years old woman with pelvic osteosarcoma Enneking 2B: - Doli Mauliate Sitompul; Yogi Prabowo (JURNAL KEDOKTERAN DAN KESEHATAN, 2017)
Pelvic osteosarcomas are considerably rare compare to other lession of osteosarcoma. The anatomic proximity of the pelvis to many neurovascular structures and the urinary and intestinal tracts become a challenge of surgical procedure during excision and reconstruction. Resectability of the tumor determined through the size, extend of the lession through the pelvic and involvement of visceral organ or local infiltration. The prognosis had also became dismal due to the danger of the surgical procedure and unsatisfying outcome postoperatively. In this report, we had follow a 33 years old woman with pelvic osteosarcoma after massive resection type I, II. Six month follow up show promising outcome though massive bleeding caused by the massive excision and reconstruction of the pelvis. This case presented is a operative procedure on pelvic osteosarcoma Enneking 2B with two step operation for resection and reconstruction, these procedure fight against massive bleeding (11 liters on the first stage), challenging anatomic reconstruction of pelvic structure to restore the function and prolonged time of operation. Non vascularized fibular graft obtained and fixated bridging the promontorium to acetabulum to restore the weightbearing axis, followed with arthrodesis of the right hip using reconplate size 3.5 mm, 14 hole. The procedure performed for the case consist of 2 stage operation. First stage, the resection consist of resection of right iliac wing and right periacetabulum region. During the procedure, the availability of packed red cell considerably important, due to massive bleeding exceeded to 11 liters. During the second stage, the reconstruction took more attention about the inflammed soft tissue.  Outcome evaluation presented postoperatively, 1 month and 6 month, show better result MSTS score on evaluation during postoperative to 6 month evaluation. Radiologic evaluation also show the conveniance fixation without any sign of reccurence.  As studies have shown that limb-salvage techniques and the amputation show no difference in terms of the survival rate of patients with malignant bone tumors, the limb-salvage techniques are now being frequently used even for cases of advanced tumors. Therefore, when an extensive operation is necessary, careful preoperative planning followed with adequate intraoperative management according to the tumor location would be helpful in reducing the danger with satisfying result.